Interactive Education Is a Guarantee of Quality (Eurasian Journal of History, Geography and Economics, 2021)
Organization of modern lessons on the program of development of school education, radical reform of the education system in the educational process on the basis of the Law “On Education”, ways to use interactive methods in all educational institutions, teacher's preparation for the lesson, methodological assistance to young teachers on the basis of the system "Teacher-Apprentice", the teacher's creativity, creative approach to the lesson.